Instytucjonalne wsparcie małych i średnich przedsiębiorstw w warunkach globalizacji - Marciszewska, Anna (Institutional support for small and medium-sized enterprises in conditions of globalization, 2005)
The article discusses issues related to institutional support for small and medium-sized enterprises in conditions of globalization. It is based on the author’s research entitled "Institutional Support for Small and Medium-sized Enterprises” which was conducted among 218 firms representing the SME sector in the region of Lower Silesia. Based on her research results, the author attempts to analyse and assess the support from the perspective of entrepreneurs and to indicate directions for the improvement of institutional support for the SME sector in Poland in conditions of increasing globalization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 157-168